The Relation between Sustained Attention and Incidental and Intentional Object-Location Memory - Efrat Barel; Orna Tzischinsky (Brain Sciences, 2020)
The role of attention allocation in object-location memory has been widely studied through incidental and intentional encoding conditions. However, the relation between sustained attention and memory encoding processes has scarcely been studied. The present study aimed to investigate performance differences across incidental and intentional encoding conditions using a divided attention paradigm. Furthermore, the study aimed to examine the relation between sustained attention and incidental and intentional object-location memory performance. Based on previous findings, an all women sample was recruited in order to best illuminate the potential effects of interest. Forty-nine women participated in the study and completed the psychomotor vigilance test, as well as object-location memory tests, under both incidental and intentional encoding divided attention conditions. Performance was higher in the incidental encoding condition than in the intentional encoding condition. Furthermore, sustained attention correlated with incidental, but not with intentional memory performance. These findings are discussed in light of the automaticity hypothesis, specifically as it regards the role of attention allocation in encoding object-location memory. Furthermore, the role of sustained attention in incidental memory performance is discussed in light of previous animal and human studies that have examined the brain regions involved in these cognitive processes. We conclude that under conditions of increased mental demand, executive attention is associated with incidental, but not with intentional encoding, thus identifying the exact conditions under which executive attention influence memory performance.